Natural durability of wood for fifteen Eucalyptus and two Corymbia species in contact with the soil - Gaeta Montagna, Ricardo; de Freitas, José Antonio; da Luz Freire Neto, Antônio Orlando; Fioruci, Wilson José; Bucci, Luís Alberto; Ranzini, Maurício; de Lima, Israel Luiz; Longui, Eduardo (Maderas. Ciencia y Tecnología, 2025)
Wood can be highly susceptible to deterioration by xylophagous agents, which compromises its structural integrity and limits its use in applications involving soil contact. Therefore, evaluating the natural durability of wood is essential to determine its most appropriate uses. The present research aimed to evaluate natural durability as a function of exposure time of 15 species of Eucalyptus and two species of Corymbia, in order to classify wood for use in contact with soil. Two fence posts and stakes of each species were installed in the Floresta Estadual de Manduri, SP. The fence posts of Eucalyptus umbra (broad-leaved white mahogany) and Corymbia citriodora (lemon-scented gum) showed the highest natural durability values, whereas Eucalyptus dunnii (dunn’s gum) and Eucalyptus grandis (rose gum) showed the lowest values. Stakes of Corymbia citriodora (lemon-scented gum) and Corymbia maculata (spotted gum) showed the highest values, whereas Eucalyptus dunnii (dunn’s gum) and Eucalyptus grandis (rose gum), again, showed the lowest values. Overall, fence posts and stakes have good natural durability against exposure up to 7 years; however, after this period, durability decreases considerably. The natural strength of both posts and stakes can be estimated as a function of exposure time with good accuracy. For most species of Eucalyptus and Corymbia, cuttings and posts had an average life exceeding 11 years under our experimental conditions.